KOMPARASI PRAKTIK GREEN ACCOUNTING PADA PERUSAHAAN DI INDONESIA: PERSPEKTIF PERUSAHAAN JASA DAN PERUSAHAAN DAGANG - Novia Rizki; Victoria K. Priyambodo; Paradisa Sukma; Ni Putu Ari Aryawati (Waisya : Jurnal Ekonomi Hindu, 2023)
This study aims to determine the similarities and differences betweenservice and trading companies' green accounting practices. PT BankMandiri (Persero) Tbk is used as a sample for service companies andPT Matahari Department Store Tbk is a sample for tradingcompanies. The method used descriptive comparative by comparingthe green accounting practices of the two companies disclosed in theirannual reports and sustainability reports. These two companies donot carry out production activities, but both provide quitecomprehensive environmental responsibilities. The two companiesrecycle waste, offer environmentally friendly products, reduce the useof plastic and paper, and work to reduce the negative effects ofgreenhouse gas emissions. The difference between the two lies inwhether or not a special team handles the environment and thedifferent components included in the details of environmentalmanagement costs.